Multifunctional Possibilities of Horizontal Vibrational Grinding Mills - L. Kuzev (International Mineral Processing Congress, 2014)
Unknown and unpopular vibrational grinding mills possibilities to horizontal working chambers have been discussed. They can be realized under normal conditions with the typical values of vibrations applied with vibrational grinding which are: vibration frequency from 15 Hz to 50 Hz, vibration amplitude to 6 mm and vibration geometry. These possibilities constantly increase involving new raw materials and processes. Vibration grinding is possible with other technological process accompanied by intensified technological processing, while the process decreases. In many cases these technological decisions are original.